Hasil Belajar Siswa: Analisis Pengaruh Kompetensi Guru, Motivasi Belajar, dan Lingkungan Belajar - Hidayat, Lutfi; Ilham Abimanyu; Didit Darmawan; Busro Muhammad Al Mursyidi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to analyze the influence of teacher competence, learning motivation, and family environment on student learning outcomes. These three variables are considered to be the main factors that interact with each other in shaping learning success. The research approach used was quantitative with a survey method, involving 35 seventh-grade students at MTs Miftahiyah Yasi Bangkalan as a sample selected randomly from a population of 75 students. Data collection was carried out through questionnaires and structured interviews using a Likert scale, then analyzed through validity, reliability, regression, and determination coefficient tests. The results of the analysis show that teacher competence, learning motivation, and family environment simultaneously and partially have a significant effect on student learning outcomes. Teacher competence reflects the quality of professionalism that affects the effectiveness of the learning process. Meanwhile, learning motivation has been proven to be the main driver in maintaining student engagement, and the family environment plays a role as the initial foundation for shaping attitudes and support for learning activities. These findings confirm that improving learning outcomes requires a holistic approach that includes integrated interventions in all three aspects. The practical implications of these research results can form the basis for the development of education policies and learning quality improvement programs that are more responsive and sustainable.